Changes in first flowering dates and flowering duration of 232 plant species on the island of Guernsey - Bock, Anna; Sparks, Tim H.; Estrella, Nicole; Jee, Nigel; Casebow, Andrew; Schunk, Christian; Leuchner, Michael; Menzel, Annette (Global change biology, 2014)
Climate change has affected plant phenology; increasing temperatures are associated with advancing first flowering dates. The impact on flowering duration, however, has rarely been studied. In this study, we analysed first flowering dates and flowering durations from a 27 year dataset of weekly flower observations on 232 plant species from the island of Guernsey in the English Channel. The aim of this study was to explore variation in trends and relationships between first flowering dates, flowering duration and temperature. We specifically looked for evidence that traits, such as life forms and phylogenetic groups, explained variation in sensitivity of first flowering and flowering duration among species. Overall trends revealed significantly earlier flowering over time, by an average of 5.2 days decade−1 since 1985. A highly significant shortening of flowering duration was observed by an average of 10 days decade−1. Correlations between first flowering, flowering duration and year varied between different species, traits and flowering periods. Significant differences among traits were observed for first flowering and to a lesser degree for flowering duration. Overall, in comparison to first flowering, more species had significant trends in flowering duration. Temperature relationships revealed large differences in strength and direction of response. 55% of the species revealed a significant negative relationship of first flowering dates and temperature. In contrast, only 19% of flowering durations had a significant negative temperature relationship. The advance in first flowering date together with a shortening of flowering duration suggests potentially serious impacts on pollinators, which might pose a major threat to biodiversity, agriculture and horticulture. Human health, in terms of pollen allergies, however, might benefit from a shortening of specific plant pollen seasons.